Association of the blood urea nitrogen to serum albumin ratio and 28-day all-cause mortality in patients with cardiac arrest: a retrospective cohort study using the MIMIC-IV database - Zhou, Gaosheng; Tan, Yayuan; Li, Xueli; Wang, Yixun; Wang, Dingdeng; Liu, Min (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe blood urea nitrogen to serum albumin ratio (BAR) has been identified as a novel indicator of both inflammatory and nutritional status, exhibiting a correlation with adverse cardiovascular outcomes.ObjectiveTo explore the association between the BAR and 28-day all-cause mortality in cardiac arrest patients who achieved return of spontaneous circulation (ROSC) and were admitted to the intensive care unit (ICU).MethodsData for patients with cardiac arrest were obtained from the Medical Information Mart for Intensive Care IV database. The outcome was 28-day all-cause mortality. Multivariable-adjusted Cox regression analysis, curve fitting, and threshold effects analysis were used to assess the relationship between the BAR and 28-day all-cause mortality in patients with cardiac arrest in the intensive care unit.ResultA total of 793 patients were included and divided into tertiles based on the BAR (Q1, Q2, Q3); 8-day all-cause mortality rates were 37.5%, 53.4%, and 63.8%, respectively (P < 0.001). A higher BAR at initial admission was significantly associated with an increased 28-day all-cause mortality risk. Results from the adjusted Models 2, 3, 4, and 5 were consistent with those of Model 1. Subgroup analysis revealed no interactions in age, sex, renal disease, liver disease, vasoactive drug use, ventilation, race, aids, malignant cancer, diabetes, peptic ulcer disease, rheumatic disease, chronic pulmonary disease, cerebrovascular disease, peripheral vascular disease, congestive heart failure and myocardial infarct between the BAR and 28-day all-cause mortality. Restricted cubic spline analysis revealed a nonlinear association between the BAR and 28-day all-cause mortality (P = 0.003). With BAR ≤ 17.981, each 1-unit increase in the BAR was associated with a 5.7% higher risk of death [95% CI (1.012–1.105), P < 0.05].ConclusionThis study identified a non-linear relationship between the BAR and 28-day all-cause mortality in patients with cardiac arrest.